Universal sex differences in the desire for sexual variety: tests from 52 nations, 6 Continents, and 13 Islands - Schmitt, David P. (2003)
Evolutionary psychologists have hypothesized that men and women possess both long-term and short-term mating strategies, with men's short-term strategy differentially rooted in the desire for sexual variety. In this article, findings from a cross-cultural survey of 16,288 people across 10 major world regions (including North America, South America, Western Europe, Eastern Europe, Southern Europe, Middle East, Africa, Oceania, South/Southeast Asia, and East Asia) demonstrate that sex differences in the desire for sexual variety are culturally universal throughout these world regions. Sex differences were evident regardless of whether mean, median, distributional, or categorical indexes of sexual differentiation were evaluated. Sex differences were evident regardless of the measures used to evaluate them. Among contemporary theories of human mating, pluralistic approaches that hypothesize sex differences in the evolved design of short-term mating provide the most compelling account of these robust empirical findings.